Policing and politics in Latin America: when law enforcement breaks the law - Esparza, Diego (Lynne Rienner Publishers, 2022)
"Challenging fundamental assumptions about the virtues of local control, considers why some Latin American countries' police forces are more corrupt than others-and what policy initiatives can turn an abusive police force into one that works for its citizens"--